Stereo- and regio-selective synthesis of silicon-containing diborylalkenes via platinum-catalyzed mono-lateral diboration of dialkynylsilanes. Issue 30 (13th March 2020) - Long, Peng-Wei; Xie, Jia-Le; Yang, Jing-Jing; Lu, Si-Qi; Xu, Zheng; Ye, Fei; Xu, Li-Wen
Abstract : A phosphine-assisted platinum-catalyzed mono-lateral diboration of dialkynylsilanes for the construction of silicon-tethered alkynyl diborylalkenes with or without silicon-stereogenic centers is described. Abstract : A highly chemoselective platinum-catalyzed mono-lateral diboration of dialkynylsilanes for the construction of silicon-tethered alkynyl diborylalkenes is described, in which tris(4-methoxyphenyl)phosphine was found to be an effective ligand for the cis -addition of diboron agents to the silicon-tethered alkynes, and the chiral ligand (AFSi-Phos)-mediated diboration of dialkynylsilanes resulted in the desymmetric construction of silicon-stereogenic centers with promising enantioselectivity.